Analysis of associated malformations by computed tomography in adults with polysplenia syndrome: A pilot study. - Xinru Gu; Shuangshuang Xu; Jinghua Chen; Xiaoqin Jiang; Ping Xie; Xiang Fang; Yan Gao; Jian Huang; Kefu Liu (PLoS ONE)
Objective To analytically depict the associated malformations of polysplenia syndrome (PS) in adults via computed tomography (CT). Materials and methods The incidence of malformations associated with PS in twelve adult patients was retrospectively analyzed via CT imaging. Results The number of splenic nodules ranged from three to twelve; the splenic nodules were located in the left upper quadrant in nine patients and in the right upper quadrant in three patients. A short pancreas was present in all twelve patients. Midgut malrotation was present in eight patients. Situs inversus totalis was present in two patients. Nine patients presented the absence of hepatic segmental inferior vena cava (IVC), with the hepatic vein directly converging into the right atrium and the continuation of the azygos vein. The preduodenal portal vein was present in six patients. Left lung heterotaxy was found in nine patients. The inferior vena cava was bilateral in one patient. Aberrant right subclavian arteries, bilateral common carotid arteries sharing trunks, abnormal renal vein branching and routing, and abdominal portal vein branching were also found in individual patients. Conclusions PS is a complex malformation syndrome involving multiple systems. The most common malformation is short pancreas, and other malformations, such as left lung heterogeneity, hepatic segmental IVC agenesis with continuation of the azygos vein, midgut malrotation, preduodenal portal vein, and left atrial heterotaxy, have relatively high prevalence rates.